2011
DOI: 10.1590/s1806-66902011000200033
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade e esverdeamento pós-colheita de tubérculos de cultivares de batata produzidos na safra de inverno

Abstract: Resumo -Cultivares de batata com bom desempenho produtivo e cujos tubérculos sejam resistentes ao esverdeamento, são de grande importância econômica para o setor produtivo. Objetivou-se com esse trabalho avaliar a produtividade, a classificação, o teor de proteína e a resistência ao esverdeamento pós-colheita de tubérculos de cultivares de batata, produzidos na safra de inverno. O experimento foi conduzido durante a safra de inverno de 2008, no município de Itaí, SP. O delineamento experimental utilizado foi o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 13 publications
3
8
0
5
Order By: Relevance
“…In this condition, the cultivar Mondial produced tubers with higher protein content. Although Lachman et al (2005) have stated that the protein content in potato tubers is affected by cultivars, fertilization systems, and crop management systems, similar to that observed in the present study, Fernandes et al (2011) found no differences in the protein content of the tubers of Agata and Mondial grown in soil with high P availability. Phosphorus fertilization did not change the tuber protein content, but increased the yield of marketable tubers, which, consequently, results in a higher protein yield per area.…”
Section: Resultssupporting
confidence: 86%
“…In this condition, the cultivar Mondial produced tubers with higher protein content. Although Lachman et al (2005) have stated that the protein content in potato tubers is affected by cultivars, fertilization systems, and crop management systems, similar to that observed in the present study, Fernandes et al (2011) found no differences in the protein content of the tubers of Agata and Mondial grown in soil with high P availability. Phosphorus fertilization did not change the tuber protein content, but increased the yield of marketable tubers, which, consequently, results in a higher protein yield per area.…”
Section: Resultssupporting
confidence: 86%
“…Misra & Kulshrestha (2003) Com relação ao esverdeamento pós-colheita, houve aumento na diferença de cor da película dos tubérculos (∆E) com o avanço do período de exposição à luz (Tabela 3). Resultados semelhantes foram obtidos por outros autores (Brune & Melo, 2001;Feltran et al, 2004a;Grunenfelder et al, 2006;Fernandes et al, 2011). Muraja-Fras et al (1994 relataram que o esverdeamento dos tubérculos expostos à luz começa no primeiro dia de exposição à luz, quando os amiloplastos presentes na película dos tubérculos iluminados começam a transformar-se em cloroplastos.…”
Section: áCido Cítrico) ---------------------------------------------unclassified
“…Na última avaliação, a intensidade de esverdeamento observada na cultivar Voyager aumentou ainda mais e passou a ser superior à verificada nas cultivares Annabelle, Ambra, Atlantic, Fontane e Markies (Tabela 3). As diferenças observadas entre as cultivares testadas estão de acordo com Grunenfelder et al (2006) e Fernandes et al (2011), que relataram que a intensidade de esverdeamento dos tubérculos de batata, quando expostos às mesmas condições indutoras, varia com a cultivar utilizada. A partir dos 15 dias de exposição, os valores de diferença de cor ficaram entre 6,0 e 12,0, ou seja, a partir dessa época todas as cultivares apresentaram variação de cor facilmente distinguível, exceto a cultivar Voyager que foi a mais sensível ao esverdeamento desde os dez dias de exposição (Tabela 3).…”
Section: áCido Cítrico) ---------------------------------------------unclassified
“…The same was observed among clones and among controls, showing that there is great genetic variability among the genotypes evaluated. Fernandes et al (2011) noted that even in cultivars commonly planted, the index is still variation among genotypes for high yield and protein.…”
Section: Resultsmentioning
confidence: 99%